Effect of Electroencephalography Spectral Edge Frequency (SEF) and Patient State Index (PSI)-Guided Propofol-Remifentanil Anesthesia on Delirium After Laparoscopic Surgery: The eMODIPOD Randomized Controlled Trial. Issue 2 (8th April 2022) - Wang, E.; Wang, Lu; Ye, Chunyan; Luo, Ning; Zhang, Yanrong; Zhong, Yugui; Zhu, Maoen; Zou, Yu; Li, Qian; Li, Longyan; Song, Zongbin; Luo, Hui; et al.
Abstract : Background: The effect of SedLine electroencephalography (EEG)-guided anesthetic care on postoperative delirium (POD) has not been studied. Methods: This single-center randomized EEG Monitoring tO Decrease the Incidence of Post-Operative Delirium (eMODIPOD) trial involved 1560 patients aged 50 years or above undergoing laparoscopic surgery. Propofol-remifentanil anesthesia was guided either by SedLine (EEG-guided care, n=779) or not (usual care, n=781). The goal of EEG-guided care was to maintain spectral edge frequency between 10 and 15 and patient state index (PSI) between 25 and 50. The primary outcome was the incidence of POD on postoperative days 1 to 5. The secondary outcomes included emergence delirium, composite moderate-to-severe complications, length of hospital stay, intensive care unit admission, 30-day hospital readmission and all-cause mortality, and intraoperative awareness. Results: Of the 1560 randomized patients, 1545 were included in the modified intention-to-treat analysis. The median propofol administered for anesthesia maintenance was 900 mg and 1000 mg in the EEG-guided and usual care groups, respectively ( P =0.21). POD occurred in 1.0% (8/771) and 1.2% (9/774) of patients in the EEG-guided and usual care groups, respectively (risk ratio: 0.89; 95% confidence interval: 0.35-2.30). There were no between-group differences in all secondary outcome measures. Emergence delirium occurred in 11.8% (91/771) and 13.2% (102/774) of the EEG-guided care and usual care groups, respectively (risk ratio: 0.90; 95% confidence interval: 0.69-1.17; P =0.41). Three patients from each group reported intraoperative awareness. Conclusions: Compared with usual care, SedLine spectral edge frequency-guided and patient state index-guided propofol-remifentanil anesthetic care neither alters anesthetic delivery nor decreases the unexpected low incidence of POD in relatively young Chinese patients undergoing laparoscopic surgery.